ULTRAVIOLETÂ -Â VISIBLEÂ ANDÂ FOURIERÂ TRANSFORM-INFRAREDÂ SPECTROSCOPICÂ STUDIESÂ ONÂ DRYNARIA QUERCIFOLIA L. RHIZOME - G, PRASANNA; R, ANURADHA (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The present study has been designed to produce ultraviolet-visible (UV-VIS) and Fourier transform-infrared (FT-IR) spectrum profile of rhizome of Drynaria quercifolia. Methods: The methanol extract was examined under visible and UV light for proximate analysis. The extract was scanned in the wavelength ranging from 100 to 1100 nm. FT-IR spectrum was also used to identify the functional groups of active components based on their peak values in the region of infrared radiation. Results: The result showed the peaks at 279 and 214 nm with the absorption 0.921 and 2.607, respectively. The result of FT-IR profile confirmed the presence of amines, alkanes, denatured amines, alkynes, carboxylic acids, alkenes, alkanes and alkenes which shows the peaks at 3436, 2197, 2360, 2125, 1772, 1626, 1447 and 815, respectively. Conclusion: The results of our study generated the UV-VIS and FT-IR spectrum profile of medicinally important plant D. quercifolia. In future, it can be used in the pharmaceutical industry for treating various diseases. Keywords: Active components, Drynaria quercifolia, Fourier transform-infrared spectrum, Functional groups, Ultraviolet - visible spectrum.